A rare case of sacroccocygeal teratoma type II with malignant yolk sac component - Reddy Syamala, Radha; Lakshmi, CVS; Kushwah, Praman (Indian Journal of Child Health, 2024)
Sacrococcygeal teratoma (SCT) is one of the most common neoplasms diagnosed prenatally. Obstetric ultrasound plays a role in the diagnosis and management of these tumors during pregnancy. In this case report, we discuss the postnatal outcome and a multidisciplinary approach in a neonate with massive SCT and preterm delivery. A 36-year-old mother with a pregnancy complicated by gestational diabetes and polyhydramnios and a large mass in the sacrococcygeal region delivered a girl child at 35+4 weeks gestation by elective cesarean section following an in utero transport to our center. The teratoma, measuring 15×12 cm, was completely excised along with the coccyx and perineum postnatally on day 3 of life. As histopathology revealed a small cluster of pre-malignant yolk sac tissue, the infant is under the care of a hemato-oncologist. Multidisciplinary care including good obstetric practices with serial monitoring with ultrasonography, in utero transfer to a center with Level III Neonatal Intensive Care, and pediatric surgery services with good nursing care result in improved outcomes in these complexes prenatally diagnosed tumors.